О влиянии микроструктуры на циклическую долговечность микрослоистых Fe/Cu, Mo/Cu и дисперсно-упрочненных Ni–Cr–Al2O3 материалов - Фирстов, С.А.; Луговской, Ю.Ф. (Видавничий дім "Академперіодика" НАН України, 2008)
Experimental dependences of the cyclic durability of microlayered and dispersion-hardened materials and aluminum alloys on the parameters of their microstructure are considered. On the basis of the ideas of the kinetic theory of strength, an equation describing the dependence of the durability on the parameters of a structure in the form of the Thompson–Beckofen equation is got.